Clinical significance of plasma osmolarity in acute heart failure in patients with ST-segment elevation myocardial infarction - L. I. Malinova; V. N. Elebergenov; S. N. Tolstov; V. A. Dudakov; T. P. Denisova (Российский кардиологический журнал)
Aim. To assess the clinical significance of plasma osmolarity and its regulation in acute heart failure in patients with ST-segment elevation myocardial infarction (STEMI) under various revascularization strategies.Material and methods. The study included patients hospitalized with a preliminary diagnosis of STEMI and clinically significant dyspnea (n=198). Plasma osmolarity was determined upon admission by estimation. To assess the intensity of vasopressin synthesis, the copeptin level was determined using an enzyme immunoassay. The study endpoints were inhospital mortality and early complications of MI.Results. The patients in the sample were comparable by sex, age, major cardiovascular risk factors and clinical phenotype of MI that served as a reason for hospitalization. The highest rate of MI early complications and inhospital mortality was among patients with initial plasma hypoosmolarity (68,6 and 40,4%, respectively). Serum copeptin levels tended to increase in patients with initially low plasma osmolarity (p=0,178). Low baseline plasma osmolarity was associated with an increased risk of death (odds ratio (OR) 0,465, 95% confidence interval (CI) 0,238; 0,911, p=0,024), mainly due to the subgroup of patients with a conservative management strategy (OR 0,335, 95% CI 0,140; 0,803, p=0,012).Conclusion. Plasma osmolarity assessed upon admission can be used to predict inhospital mortality in patients with acute heart failure and STEMI.